Awareness and Practice of Infection Control among Selected Sample of Dental Students in Saudi Arabia - Alanoud AlJubair, Bashaer Alenazi, Latifa Alolah, Dalal AlSaadoun, Hessa AlHazza’a,; AlShammery, Deema; AlGhamdi, Wejdan (International Journal of Innovative Research in Medical Science, 2017)
Cross infection control is an infectious agent transmitted within the clinical environment between patients and staff, Dental education and proper training of dental student is the major role to protect patients and dental students, to create a safe environment by facilitate immunization and help dental students to have good knowledge and attitudes toward the infection control. Objective: to Analyze and evaluate the knowledge, attitudes and practice toward infection control and infectious diseases among dental students in Saudi Arabia. Material and methods: It is a cross sectional study conducted on senior undergraduate dental students among different dental school in Saudi Arabia. An online survey was developed using surveymonkey.com. Consist of 20 questions related to hepatitis B vaccination and serology, the use of personal protective equipment, infection control practices and awareness, percutaneous and mucous membrane exposure, and attitudes toward the dental treatment of infected patients. Data was performed using SPSS version 20. Result: A total of 329 students participated in this study, the majority of students were highly aware about the meaning of infection 98.2%, infection control protocol 96.7%, and that infection can be transmitted by blood 98.5%, saliva 97.3%, and equipment 93.6%. Majority of respondent reported that AIDS and hepatitis can be spread in the clinic during treatment. With regards to vaccination, 87.5% had been vaccinated against hepatitis before entering the clinic. Although 65.3% of the students reported that they receiving enough training of infection control protocol in their college, only 51.7% were aware about the management protocol of dealing with AIDS patients. Conclusion: Although the awareness of dental students toward the infection control protocol were high, but the awareness about the management protocol of dealing with AIDS patients were low. Dental School should provide more courses and training about the policy of infection control.